2020
DOI: 10.3390/agronomy10091419
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Alleviates Temperature Stresses in Poinsettia by Regulating Stomata, Photosynthesis, and Oxidative Damages

Abstract: The effects of silicon (Si) on temperature stresses were investigated in poinsettia. Well-rooted cuttings supplemented with and without Si were exposed to 40 °C, and plants treated with or without Si during cutting propagation and cultivation were subjected to 4 °C. The results showed that almost all the stomata of cuttings without Si supplementation were closed, while some of them were still open in cuttings supplemented with Si under a high temperature stress. However, Si was not able to alleviate stomatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Our findings revealed that applications of ‘Keunson’ significantly upgraded plant growth and development, involving the shoot length, leaf length and width, and stem and bud diameters, irrespective of the cultivars ( Table 1 ). This was in line with our lab’s previous study and once gain confirmed the promising role of Si [ 35 ]. More importantly, the F -test data displayed a robust interaction between the Si applications and the diameters (stem and bud), where a vigorous stem was less susceptible to wilting during vase life.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings revealed that applications of ‘Keunson’ significantly upgraded plant growth and development, involving the shoot length, leaf length and width, and stem and bud diameters, irrespective of the cultivars ( Table 1 ). This was in line with our lab’s previous study and once gain confirmed the promising role of Si [ 35 ]. More importantly, the F -test data displayed a robust interaction between the Si applications and the diameters (stem and bud), where a vigorous stem was less susceptible to wilting during vase life.…”
Section: Discussionsupporting
confidence: 93%
“…The excessively introduced potassium from K 2 SiO 3 in 0:100, 50:50, and 100:0 treatments were deducted from KNO 3 , K 2 SO 4 , and K 2 SO 4 , respectively, and the resultant losses of nitrate and sulfate were compensated with nitric and sulfuric acid. In specific, three ratios of NH + 4 :NO − 3 solutions with an increasing NH + 4 concentration but following a constant nitrogen (N) supply at 13.0 meq•L −1 , were designed, namely 0:100, 50:50, and 100:0, according to the modified MNS (multipurpose nutrient solution); the optimized Si concentration at 1.0 meq•L −1 was chosen in this study following our pioneer publications (Park et al, 2018;Hu et al, 2020). The treatment solutions were applied every 2 days for 22 days (39 DAS).…”
Section: Treatment Solutionsmentioning
confidence: 99%
“…Under these conditions increased ROS generation is common, including more intense lipid peroxidation, which results from imbalance between production and scavenging (Jaleel et al, 2009). Hu et al, (2020) reported that Si supply during high temperature (40 °C) stress kept stomata open in poinsettia plants.…”
Section: Effects Of Silicon In Abiotic Stressesmentioning
confidence: 99%